2018
DOI: 10.3390/ma11050715
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Controlled Low Strength Material with Circulating Fluidized Bed Combustion Ash and Recycled Aggregates

Abstract: This study aims to investigate the effect of adding circulating fluidized bed combustion (CFBC) ash, desulfurization slag, air-cooled blast-furnace slag and coal bottom ash to the controlled low-strength material (CLSM). Test methods include slump flow test, ball drop test, water soluble chloride ion content measurement, compressive strength and length change measurement. The results show that (1) the use of CFBC hydration ash with desulfurization slag of slump flow is the best, and the use of CFBC hydration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Samples were compared with standard Portland cement mortar in terms of mechanical properties, permeability and microstructure. The proposed material is intended to be used as a controlled low-strength material, pervious concrete, reinforced recycled concrete and for other engineering applications [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Samples were compared with standard Portland cement mortar in terms of mechanical properties, permeability and microstructure. The proposed material is intended to be used as a controlled low-strength material, pervious concrete, reinforced recycled concrete and for other engineering applications [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Its absolute density is 1760 kg/m 3 . This value is low compared to natural aggregates such as silica sand which has an absolute density of 2600 kg/m 3 [28], and BA tested in [9] with an absolute density of 2560 kg/m 3 , but very close to the value for BA of 1880 kg/m 3 reported in [30]. In Table 2 from Reference [2] values ranging between 1390 and 2470 kg/m 3 are shown.…”
Section: Resultsmentioning
confidence: 60%
“…They stated that a ternary binder possessed strength values comparable to those of Portland cement. Lin et al [22] investigated the properties of controlled low strength material with circulating fluidized bed combustion ash and recycled aggregates. They showed that CFBC hydrated ash resulted in a higher compressive strength when compared with desulfurized slag, but had a lower compressive strength than coal bottom ash.…”
Section: Introductionmentioning
confidence: 99%